LECTURERS’ BARRIERS IN TEACHING SPEAKING SKILL DURING ONLINE AT ENGLISH EDUCATION PROGRAM - Diana Eriani; Agung Suhadi (Teaching English and Language Learning English Journal, 2023)
This research specifically explores the barriers as experienced by English lecturer in teaching speaking skill during online learning at English Study Program Muhammadiyah University of Bengkulu. This study is a descriptive analysis with phenomenological approach, which conducts in-depth interview towards five students and lecturers who were following speaking class during online learning. The results demonstrate the barriers faced in teaching speaking online namely unstable connection of internet media, not good the quality of video, not all students can access internet media and choose media for learning. Moreover, can not give feedback directly, students do not understand the material, and lecturers cannot develop the method. Furthermore, teaching targets, students cannot understand the material, and lecturers can not evaluate students performance directly. The conclussion obtains the barriers that faced by internet connection unstable, the quality of video, many students can access the media, cannot give feedback directly, don’t understand the material and lecturers cannot vary the method. Students cannot understand the materials and evaluate students performance directly. Keywords: Barriers, Teaching, Speaking, Online, Learning.